(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Wound healing is a complex, multistage process involving inflammation control, cell migration/proliferation, and extracellular matrix remodeling. Natural products offer promising candidates for wound repair due to their phytochemical diversity and multitarget pharmacology. This study investigates the in vitro wound healing activity and explores the potential mechanisms of action of ethanol extract from Phytolacca octandra leaves using network pharmacology. The in vitro wound healing potential was evaluated using a wound/scratch-based model to assess the ability of the extract to promote wound closure. Different concentrations of the ethanol extract were tested, and wound healing efficiency was compared against appropriate controls. The extract showed concentration-dependent activity, indicating that components of P. octandra may enhance cellular processes essential for tissue repair, such as migration and proliferation. To provide mechanistic insight, a network pharmacology strategy was applied to identify possible bioactive compounds and their molecular targets. Phytochemical candidates were screened based on drug-likeness criteria, and potential targets were predicted using established databases. Targets were integrated into protein–protein interaction (PPI) networks to determine hub genes and key interaction nodes. Functional and pathway enrichment analyses were then performed to identify biological processes and signaling pathways relevant to wound healing. The predicted mechanism suggests that the extract may act through multiple pathways associated with inflammatory regulation, oxidative stress modulation, extracellular matrix reorganization, and cell cycle/cellular migration events.